Civic agency in Africa arts of resistance in the 21st century - Obadare, Ebenezer; Willems, Wendy; Chabal, Patrick 1951-2014 (Boydell & Brewer, 2014)
The recent wave of popular protests across North Africa and the Middle East has stimulated debate on the meaning and strategies of resistance in the 21st century. One key factor to emerge has been the absence of formal organizations in effecting the transformation of these states. To date, the literature on resistance in civil society in Africa has been dominated by exploration of the dynamics of formal NGOs, but this fails to take account of the changinglandscape of social change unfolding on the continent and the importance of both the local and informal. This book takes as its starting point what is actually happening on the ground, the expressions of resistance in thenon-governmental sphere and the various socio-economic, political, and artistic praxes that animate it. It examines the variety of organized and unorganized ways in which Africans exercise agency and resist state power. The bookevaluates the meaning of resistance and the politics of citizen action in Africa today; the way in which resistant practices impinge on the state and the kinds of state formations that are emerging as a response to citizen action;the use of popular culture as modes of resistance; and the power of cultural belonging in the public sphere. The book does not merely explore these practices but how agency and resistance engage, transform, co-opt, undermine, reproduce or reinforce the post-colonial African state. Ebenezer Obadare is Associate Professor, Department of Sociology, University of Kansas; Wendy Willems is Lecturer in Media, Communication and Development in the LSE Department of Media and Communications. She was previously Senior Lecturer and Head of Department of Media Studies at the University of the Witwatersrand (2010-2012), where she remains affiliated as an Honorary Research Fellow